IMPLEMENTASI MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA SEKOLAH DASAR ( Studi Eksperimen di Kelas IV SD Negeri 008 Salo Kabupaten Kampar ) - Nurma Suwasti Nurma Suwasti; Hendri Marhadi Hendri Marhadi; Zufriady Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problems in research is whether there are significant differences between the results of student learning that received the application of learning model snowball throwing and students who obtain lessons learned ordinary class 4 SDN 008 Salo. This study aims to to perceive the difference between study results social class students who have the application of learning model Snowball Throwing and students who obtain lessons learned ordinary, in the specific case of material technology development. As for benefits this research, is one effort to increase yields of learning and could become one of the alternative learning. Of research in class IVa and IVb , namely in sdn 008 salo kabupaten kampar. The study is done at may 2015. This research is study experiment in the form of quantitative the data types figures. The sample forty-two students. The result of the research is the average value students got from the student learning control class increased. Than the average pretes 60.92 be 66.69 in the average a score postes. When viewed from n-gain reached 0.14 categorized as low. For the experiment class also has increased from average pretes 65.42 be 79.73 on average postes value. When viewed from n-gain reached 0.32 including medium category. After tested the difference, found that the increase in value average second-class having the difference significant , if seen in control class the enhancement of value average namely 5.77 or ranged 9.47 % and experiment class increase in value averagenamely 14.31 or ranged 21.87 % .Key words : snowball throwing, control class, experiment class, pretest, postest, N-gain